Implementing Strategic Environmental Assessment (SEA) in the Global South, a challenge: Nicaragua as a case study. - Díaz Canales, Edith Benjamina; Avila , Alfredo; Schlüter, Sabine; Lacayo, Erick; Schlüter, Alexander (19th Conference on Sustainable Development of Energy, Water and Environment Systems)

Vorwort - Herzig, Bardo; Eickelmann, Birgit; Schwabl, Franziska; Schulze, Johanna; Niemann, Jan (Lehrkräftebildung in der digitalen Welt Zukunftsorientierte Forschungs- und Praxisperspektiven)

Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven

Anthropological Dimension of Wartime Ecocide: Ecofeminist Methodological Assessments - Karpenko, Kateryna I.; Hagengruber, Ruth Edith; Nielsen, Cynthia R. (Anthropological Measurements of Philosophical Research)
The authors aim to disclose the anthropological dimension of ecocide during and after Russia’s war against Ukraine, relying on the multidisciplinary practices and intellectual production of ecofeminist women thinkers, including philosophers, sociologists, historians, psychologists, and others. The theoretical basis methodological approaches in philosophical anthropology, phenomenology, analytical philosophy, communicative philosophy, existentialism, ethics of justice, and ethics of care determine the study’s theoretical basis. Originality. For the first time, a systematic analysis of the anthropological dimension of ecocide has been carried out based on ecofeminist methodology. The specifics of the Ukrainian resistance to ecocide were revealed as part of a single struggle – an anti-imperial and ecological struggle for independence and prosperity. It is emphasized that during the war, the opposition to ecocide is a component of the fight for national sovereignty and territorial integrity of the country, and therefore, the ideas of pacifism in this period are subordinated to this primary goal. After the war, preventing threats of ecocide should become an integral part of the struggle for stable peace and prosperity. Ecofeminist pacifist perspectives should be a priority among the most essential goals for that period. Conclusions. Ecofeminist methodological assessments offer valuable insights into the anthropological dimension of ecocide in wartime and post-war contexts, highlighting the complex interplay between gender, violence, and environmental destruction. By focusing on the experiences and perspectives of women and marginalized communities, ecofeminist analyses contribute to a more holistic understanding of ecocide and its impacts on both human populations and ecosystems.

Teaching Women Philosophers—Ideas and Concepts from Women Philosophers’ Writings Over 2000 Years - Hagengruber, Ruth Edith (Teaching Women Philosophers. Women in the History of Philosophy and Sciences.)
Why should the philosophy of the Pythagoreans be reduced to Pythagoras alone? Why do we learn about the ego only from Husserl and not from Conrad-Martius? What do we know about free will from Helene Druskowitz and why is Émilie Du Châtelet unknown to us? Many of the philosophers in this collection were celebrities in their own time. What can we gain from rediscovering the knowledge of women philosophers? Philosophy reflects the foundations on which we organise our world. There is no doubt that women create structures that shape our world. Over the centuries, women thinkers have formulated ideas and concepts to explain our world and to call for its reorganisation. This collection offers a selection of these ideas and concepts from over 2000 years. The new history of philosophy emerges in this way. It provides the basis for teaching and future research. Rooted in the past, it can use that experience to contribute to a new and better way forward.

Teaching Women Philosophers

Understanding the Wettability of C1N1 (Sub)Nanopores: Implications for Porous Carbonaceous Electrodes - Lamata‐Bermejo, Irene; Keil, Waldemar; Nolkemper, Karlo; Heske, Julian; Kossmann, Janina; Elgabarty, Hossam; Wortmann, Martin; Chorążewski, Mirosław; Schmidt, Claudia; Kühne, Thomas D.; Lopez Salas, Nieves; Odziomek, Mateusz (Angewandte Chemie International Edition)
Abstract Understanding how water interacts with nanopores of carbonaceous electrodes is crucial for energy storage and conversion applications. A high surface area of carbonaceous materials does not necessarily need to translate to a high electrolyte‐solid interface area. Herein, we study the interaction of water with nanoporous C 1 N 1 materials to explain their very low specific capacitance in aqueous electrolytes despite their high surface area. Water was used to probe chemical environments, provided by pores of different sizes, in 1 H MAS NMR experiments. We observe that regardless of their high hydrophilicity, only a negligible portion of water can enter the nanopores of C 1 N 1 , in contrast to a reference pure carbon material with a similar pore structure. The common paradigm that water easily enters hydrophilic pores does not apply to C 1 N 1 nanopores below a few nanometers. Calorimetric and sorption experiments demonstrated strong water adsorption on the C 1 N 1 surface, which restricts water mobility across the interface and impedes its penetration into the nanopores.

35 challenges in materials science being tackled by PIs under 35(ish) in 2024 - Lázaro, Isabel Abánades; Anastasaki, Athina; Ardoña, Herdeline Ann M.; Arguilla, Maxx Q.; Bati, Abdulaziz S.R.; Batmunkh, Munkhbayar; Besford, Quinn A.; Browne, Michelle P.; Bryant, Saffron J.; Carlotti, Marco; Contini, Claudia; Delaney, Colm; et al. (Matter)

Template‐Induced Graphitic Nanodomains in Nitrogen‐Doped Carbons Enable High‐Performance Sodium‐Ion Capacitors - Li, Chun; Song, Zihan; Liu, Minliang; Lepre, Enrico; Antonietti, Markus; Zhu, Junwu; Liu, Jian; Fu, Yongsheng; Lopez Salas, Nieves (ENERGY & ENVIRONMENTAL MATERIALS)
Sodium‐ion capacitors (SICs) have great potential in energy storage due to their low cost, the abundance of Na, and the potential to deliver high energy and power simultaneously. This article demonstrates a template‐assisted method to induce graphitic nanodomains and micro‐mesopores into nitrogen‐doped carbons. This study elucidates that these graphitic nanodomains are beneficial for Na + storage. The obtained N‐doped carbon (As8Mg) electrode achieved a reversible capacity of 254 mA h g −1 at 0.1 A g −1 . Moreover, the As8Mg‐based SIC device achieves high combinations of power/energy densities (53 W kg −1 at 224 Wh kg −1 and 10 410 W kg −1 at 51 Wh kg −1 ) with outstanding cycle stability (99.7% retention over 600 cycles at 0.2 A g −1 ). Our findings provide insights into optimizing carbon's microstructure to boost sodium storage in the pseudocapacitive mode.

Synergistic design of high-performance symmetric supercapacitor based on iron oxide nanoplatelets/COOH-MWCNTs heterostructures: DFT computation and experimental analysis - Mohamed, Sayed R.E.; Mohammed, Ahmed S.A.; Metwalli, Ossama I.; El-Sayed, S.; Khabiri, Gomaa; Hassan, Abdelwahab; Yin, Kai; Abdellatif, Sameh O.; Lopez Salas, Nieves; Khalil, Ahmed S.G. (Journal of Alloys and Compounds)

Crystal engineering and sorption studies on CN- and dipyridyl-bridged 2D coordination polymers - Nguepmeni Eloundou, Valoise Brenda; Kenfack Tsobnang, Patrice; Kamgaing, Theophile; Gogoi, Chiranjib; Lopez Salas, Nieves; Bourne, Susan A. (CrystEngComm)
Structure–property relationships were studied in two coordination polymers {[Ni(bpe)(H 2 O) 2 ][Ni(CN) 4 ]·2 H 2 O} n and {[Cu(bpe)(H 2 O) 2 ][Ni(CN) 4 ]·ethanol} n . We show that the length of the ligand does not control the synthesis of Hofmann-type polymers.

Value-added utilization of biowaste-derived lignin towards the synthesis of oxygen-enriched hierarchical laser-induced graphene and its application as a micro-supercapacitor - Katwesigye, Samuel; El-Khouly, Mohamed E.; Lopez Salas, Nieves; Khalil, Ahmed S.G. (Journal of Energy Storage)

Sulfur and nitrogen co-doping of peanut shell-derived biochar for sustainable supercapacitor applications - Makinde, Wasiu Olakunle; Hassan, Mohsen A.; Pan, Ying; Guan, Guoqing; Lopez Salas, Nieves; Khalil, Ahmed S.G. (Journal of Alloys and Compounds)

Beyond Conventional Carbon Activation: Creating Porosity without Etching Using Cesium Effect - Li, Jiaxin; Xu, Yaolin; Li, Pengzhou; Völkel, Antje; Saldaña, Fernando Igoa; Antonietti, Markus; Lopez Salas, Nieves; Odziomek, Mateusz (Advanced Materials)
Abstract Facile synthesis of porous carbon with high yield and high specific surface area (SSA) from low‐cost molecular precursors offers promising opportunities for their industrial applications. However, conventional activation methods using potassium and sodium hydroxides or carbonates suffer from low yields (<20%) and poor control over porosity and composition especially when high SSAs are targeted (>2000 m 2 g −1 ) because nanopores are typically created by etching. Herein, a non‐etching activation strategy is demonstrated using cesium salts of low‐cost carboxylic acids as the sole precursor in producing porous carbons with yields of up to 25% and SSAs reaching 3008 m 2 g −1 . The pore size and oxygen content can be adjusted by tuning the synthesis temperature or changing the molecular precursor. Mechanistic investigation unravels the non‐classical role of cesium as an activating agent. The cesium compounds that form in situ, including carbonates, oxides, and metallic cesium, have extremely low work function enabling electron injection into organic/carbonaceous framework, promoting condensation, and intercalation of cesium ions into graphitic stacks forming slit pores. The resulting porous carbons deliver a high capacity of 252 mAh g −1 (567 F g −1 ) and durability of 100 000 cycles as cathodes of Zn‐ion capacitors, showing their potential for electrochemical energy storage.

Revisiting the phosphonium salt chemistry for P-doped carbon synthesis: toward high phosphorus contents and beyond the phosphate environment - André, Rémi F.; Gervais, Christel; Zschiesche, Hannes; Jianu, Teodor; Lopez Salas, Nieves; Antonietti, Markus; Odziomek, Mateusz (Materials Horizons)
Calcination of THPC–urea in metal chloride hydrate salt affords porous P/N-doped carbonaceous materials (up to 18 wt% [P]), used as oxidative dehydrogenation catalysts.

Novel onion flower-derived biochar for high-performance sustainable supercapacitor applications - Kwarteng, Felix A.; Abdel-Aty, Ahmed A.R.; Mohamed, Sayed R.E.; Hassan, Mohsen A.; Ohashi, Hidenori; Lopez Salas, Nieves; Semida, Wael M.; Khalil, Ahmed S.G. (Diamond and Related Materials)

Electrifying the field of metasurface optics - Güsken, Nicholas Alexander; Brongersma, Mark L. (Photonics Insights)

Elektrooptische PLL - Kruse, Stephan; Scheytt, J. Christoph

Internationale Solidaritätsgemeinschaften als Handlungsmodelle in der Exil-Kinder- und Jugendli-teratur am Beispiel von Jella Lepmans „Das Geheimnis vom Kuckuckshof“ (1942) - Jagdschian, Larissa Carolin (Jella Lepman. Journalistin, Autorin, Gründerin der Internationalen Jugendbibliothek. Eine Wiederentdeckung)

Florian Krobb: „Afrikas Zukunft“. Jugend- und Abenteurliteratur in Deutschlands „afrikanischem Jahrhundert“ (1840-1940) - Jagdschian, Larissa Carolin